Komunikasi Terapeutik Guru Pada Siswa Berkebutuhan Khusus SLB Karabela (Down Syndrome) Kota Bengkulu (Studi Di Sekolah Luar Biasa Negeri Karabela) - Dianthi, Martha Heriniazwi; Narlena, Iis; Yanto, Yanto (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This research was conducted to find out how the stages in therapeutic communication process are established between teachers and students with Down syndrome who are in SLB Karabela, Bengkulu city. This research uses descriptive qualitative methods. In this study using data collection techniques through in-depth interviews, observation, and documentation. The results showed that there is a practice of therapeutic communication at SLB Karabela, where this communication has four stages, namely the pre-interaction stage where this stage the teacher prepares himself to meet with students, the stage (orientation) Introduction stage where the teacher approaches students slowly, the work stage where the teacher is teaching children with Down syndrome by persuading students gently and the termination stage where the teacher sees the students’ development from beginning to end. In this study it is found that teachers in dealing to students with Down syndrome have different ways. This is because students with Down syndrome have different characters, so they require different actions.